A community- based hepatitis B linkage-to-care program: a case study on Asian Americans chronically infected with hepatitis B virus. Issue 1 (December 2016) - Hyun, Chul; Ventura, William; Kim, Soon; Yoon, Soyoung; Lee, Seulgi
Abstract Background Hepatitis B is an important disease of ethnic disparity which affects Asian Americans and other minority populations disproportionately. Despite the high prevalence of hepatitis B in Asian Americans, many of them remain unscreened and untreated. A majority of the individuals chronically infected with hepatitis B virus (HBV) are not linked to care, for instance, due to a lack of culturally competent programs. There are many serious barriers preventing linkage to care (LTC), including personal, socio-cultural, and economic issues. The purpose of this study was to evaluate various barriers affecting LTC and to investigate the role and efficacy of a community-based Patient Navigator (PN) program in expediting LTC and in improving health outcomes for hepatitis B patients in a high risk population. Methods A total of 45 individuals chronically infected with HBV were identified through community screening events and were subsequently linked to patient navigators (PN), who then arranged for the patients to have a medical evaluation with a provider of their choice in their communities. The navigators kept detailed records of the patients' progress towards goal, and planned follow up visits for each patient. A self-report questionnaire was employed to assess patients' demographics, history of HBV infection, and barriers in accessing health care. Specifically, the levels of importance of the barriers due to language, culture, financial reasons were assessed. Results The study revealed that 38 of the 45 HBV infected individuals knew about their infection status from previous screening. Forty two out of 45 HBV infected individuals were linked to care within a 12 month period, demonstrating a high linkage rate. Most significant barriers identified were language and finance, followed by cultural barrier and others. Conclusion There are specific barriers to accessing adequate care for the patients affected by chronic hepatitis B (CHB) in Korean American community. The implementation of a PN program in conjunction with the community network of health care providers may help to overcome the barriers and facilitate LTC in hepatitis B.